Reuse of CO2 in energy intensive process industries - Perathoner, Siglinda; Van Geem, Kevin M; Marin, Guy B; Centi, Gabriele (Chemical communications (Cambridge, England), 2021)
Closing the carbon cycle and enabling a carbon circular economy in energy intensive industries (iron and steel, cement, refineries, petrochemistry and fertilizers) are topics of increasing interest to meet the demanding target of defossilizing the production. The focus of this perspective contribution is on CO2 reuse technologies in this context. While this is a topic with abundant literature, the analysis of applying CO2 reuse technologies evidences the need to go beyond those receiving most of the attention today, such as conversion of CO2 to methanol. Depending on the specific context, different scenarios are expected. Some examples illustrating the search for novel solutions are provided, such as those starting from the efficient conversion of CO2 to CO. Once CO is produced from CO2 many bio-chemical and catalytic conversion routes open up next to direct uses of CO in the steel and chemical sector.Closing the carbon cycle and enabling a carbon circular economy in energy intensive industries (iron and steel, cement, refineries, petrochemistry and fertilizers) are topics of increasing interest to meet the demanding target of defossilizing the production. The focus of this perspective contribution is on CO2 reuse technologies in this context. While this is a topic with abundant literature, the analysis of applying CO2 reuse technologies evidences the need to go beyond those receiving most of the attention today, such as conversion of CO2 to methanol. Depending on the specific context, different scenarios are expected. Some examples illustrating the search for novel solutions are provided, such as those starting from the efficient conversion of CO2 to CO. Once CO is produced from CO2 many bio-chemical and catalytic conversion routes open up next to direct uses of CO in the steel and chemical sector.